Study The Impact of Geopolymer Mortar Reinforced by Micro Steel Fibers (Journal of Engineering, 2022)
In this research, geopolymer mortar had to be designed with 50% to 50% slag and fly ash with and without 1% micro steel fiber at curing temperature of 240℃. The molarity of alkaline solution adjusted with 12 molar sodium hydroxid to sodium silicate was 2 to 1, reaspectivly. The heat of curing increased the geopolymerization proceses of geoplymer mortar, which led to increasing strength, giving the best result and early curing age. The heat was applied for two days by four hours each day. It was discovered in the impact test that the value first crack of each mix was somewhat similar, but the failure increased 72%  for the mixture that did not contain fiber. For the energy observation results it was shown that the mixtures with fiber increased by about 40% compared with the mixtuers without fibers at the first crack and 72% at the failure, respectively.